Work symbolic motive scale: development and validation of a measure of affective investment at work. (2018) - Fregonese, Chiara; Caputo, Andrea; Langher, Viviana
The general aim of this paper is to propose a conceptualisation and an operational measure for affective investment and symbolic motives at work. The work-symbolic motive scale (Work-SMS) score provides a general measure of affective investment, conceived as an endowing process of gratifying qualities to the work context, sustained by the four symbolic motives of achievement, affiliation, power and autonomy. Two studies were conducted (N = 632) suggesting a final 12-item scale with a second-order factor model. Evidence for construct and convergent validity was collected and overall good internal consistency, test-retest reliability estimates and predictive validity after one month were verified.